Alquran communication patterns and efforts to build positive communication - Iman Sumarlan; Rizki Firmansyah; Hendra Darmawan (Journal of Social Studies (JSS), 2021)
Communication is an important matter in social life in building understanding and togetherness. This study aims to analyze the pattern of positive communication in the Alquran. This research paper uses a qualitative with analisys texts method, with a descriptive and interpretative approach to obtain clear information from the Alquran in communicating. Human relations are not built properly if they ignore the values and main aspects of communicating, namely honesty, truth, and clarity. All aspects that in recent years have diminished and may have disappeared. Alquran as a holy book contains kalamullah as a form of communication to humans which is loaded with various communication messages so that it can be used as a guide for humans to interact because the Alquran presents an ideal picture in communicating. This study uses a qualitative approach with a analisys teks method from the book of commentaries and sources with other similar topics.